ANALISIS PENGENDALIAN KUALITAS PRODUK MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL (SQC) DI PLANT D DIVISI CURING PT. GAJAH TUNGGAL, Tbk. - Puji Rahayu (Jurnal Teknik, 2020)
ABSTRACTPT. Gajah Tunggal Tbk, is a manufacturer of car and motorcycle tires that always tries to increase production productivity to meet customer-customer demand from automotive companies. Based on data obtained from PT. Gajah Tunggal Tbk., The problem that most affected this year's production productivity was the problem defect, and there was an increase in defects exceeding the monthly defect target this year in March to May 2018. In this study quality improvement efforts were carried out using Statistical Quality Control (SQC) method . The analysis is carried out using several tools from seven tools namely fishbone diagram, pareto diagram, and P control chart (P-Chart). Based on the Pareto diagram, it is known that the most dominant defect that occurs in March-May 2018 is the type of dedect Under Cure. Then the causes of the product defect were analyzed using Fishbone diagramming tools. After the cause of the defect is known, then a repair recommendation is made using the 5W + 1H concept. then made a P control chart for the proposed standard defect per day. Keywords: SQC, Quality Control, Defect, Seven Tools, Production Productivity.